1999
DOI: 10.1002/(sici)1520-6300(199911/12)11:6<735::aid-ajhb3>3.0.co;2-1
|View full text |Cite
|
Sign up to set email alerts
|

Somatic comparisons at four ages of South Korean females and females of other Asian groups

Abstract: Somatic data were collected during April 1997 on 156 females ages 6, 9, 13, and 15 years, residing in urban Pusan, South Korea, and on 158 age peers residing in rural regions surrounding the city. Comparisons were made between urban and rural groups for measures of body size and form, skinfold thicknesses, the body mass index (BMI), and estimated arm muscle area (ARM). Age at menarche was retrospectively reported by the 13‐ and 15‐year‐olds. The data were analyzed in 2 (urban‐rural) × 3 (age) analyses of varia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
5
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 31 publications
2
5
0
Order By: Relevance
“…Sex related effects might be controlling muscularity of boys and girls and it is the reason behind greater muscularity of boys. Similar trends were reported among Indian (Chowdhury and Ghosh 2009;Basu et al 2010;Sen et al 2011;Sen and Mondal 2013;Singh and Mondal 2014), Argentinean (Bolzan et al1999), South Korean (Kim et al 1999), Kenyan (Semproli and Gualdi-Russo 2007), Zimbabwean (Olivieri et al 2008), Turkish ) and Nigerian (Senbanjo et al 2014) children. The comparison of age-and sex-specific mean values of muscularity of children of the present study with their American counterparts (Frisancho 1981) reflects a very poor nutritional status.…”
Section: Discussionsupporting
confidence: 79%
“…Sex related effects might be controlling muscularity of boys and girls and it is the reason behind greater muscularity of boys. Similar trends were reported among Indian (Chowdhury and Ghosh 2009;Basu et al 2010;Sen et al 2011;Sen and Mondal 2013;Singh and Mondal 2014), Argentinean (Bolzan et al1999), South Korean (Kim et al 1999), Kenyan (Semproli and Gualdi-Russo 2007), Zimbabwean (Olivieri et al 2008), Turkish ) and Nigerian (Senbanjo et al 2014) children. The comparison of age-and sex-specific mean values of muscularity of children of the present study with their American counterparts (Frisancho 1981) reflects a very poor nutritional status.…”
Section: Discussionsupporting
confidence: 79%
“…However, the benefit seems to have been unequally distributed as the rate of increase in height appears to have been substantially greater for urban compared with rural dwellers. Rural–urban differences in height have been reported in European24 25 and Asian26 27 populations but, at least in the European studies, height differences by locale appear to be decreasing rather than increasing. However, in Thailand increasing income inequality between rural and urban populations has been apparent from the 1960s through to at least the early 1990s,13 spanning the years in which the majority of our cohort members were children.…”
Section: Discussionmentioning
confidence: 97%
“…The height of Japanese boys between 1950 and 1960 peaked at a dramatic increment of 8 cm per decade at the age of 14 years. In Korean children (Spurgeon et al 1997;Kim et al 1999) the reported increment approximated 2.1-2.6 cm/decade at age 9 years, 1.9-3.7 cm/decade at age 15 years. The secular increase in body weight was reported as 0.7 kg/decade and 0.6 kg/decade in Belgian boys and girls at the age of 18 years between 1830 and 1980 (Susanne and Bodzsar 1997), 1.2 kg/decade and 1.1 kg/decade in Australian adults during the last 100 years (Loesch et al 2000), which was lower than or close to that of Mongolians.…”
Section: Discussionmentioning
confidence: 96%